Comparison of 99mTc Injected Activity with Prescribed Activity in Four Types of Nuclear Medicine Exams - Khan, Muhammad I.; Farwa, Umme; Iqbal, Tahir; Ali, Saadat; Nazir, Aalia; Ijaz, Mohsin (Current Radiopharmaceuticals, 2020)
Background: 99mTc is a radioactive isotope that is obtained by eluting a 99Mo/99mTc generator. (PINSTECH, Islamabad) and used for radionuclide scanning. Objectives: The objective of this work is to study the uncertainties in 99mTc activity that exist due to time delay between injection preparation and administration to patients, during the process of gamma camera scanning. Methods: Lead canisters were used for storing elution vials and dose calibrator for measuring 99mTc activity in mCi. The activity of preparing 99mTc injection and its administration to patients were compared with the prescribed values of activity recommended in the Society of Nuclear Medicine procedure guidelines. Results: This study showed that uncertainty in the activity existed in one thyroid patient, 38 bone patients, 5 renal patients and 45 cardiac patients. Conclusion: This uncertainty in activity exists due to time delay between injection preparation and administration to patients, as well as due to residual radionuclide that is not injected into patients and remains in the syringe.
Keywords: bone scintigraphy